2020
DOI: 10.12701/yujm.2020.00157
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives in stem cell therapies for osteoarthritis of the knee

Abstract: Mesenchymal stem cells (MSCs) are emerging as an attractive option for osteoarthritis (OA) of the knee joint, due to their marked disease-modifying ability and chondrogenic potential. MSCs can be isolated from various organ tissues, such as bone marrow, adipose tissue, synovium, umbilical cord blood, and articular cartilage with similar phenotypic characteristics but different proliferation and differentiation potentials. They can be differentiated into a variety of connective tissues such as bone, adipose tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…There is induced production of interleukin-1 receptor antagonist (IL-1Ra) molecule in significant concentration by the MSCs and these produced molecules execute the bioactivity of inhibiting IL-1 catabolism (12). This interesting biological approach renders symptomatic relief in pain (13,14). MSCs also support neoangiogenesis through VEGF-A, VEGF-D, HGF, IGF-1, PDGF, PIGF, IL-6, EPO, MCP-1 and cellular proliferation through KGF, FGF-2, VEGF, IGF, PDGF, HGF (11,14).…”
Section: Physiology Of Msc Action In Oa Kneementioning
confidence: 99%
See 2 more Smart Citations
“…There is induced production of interleukin-1 receptor antagonist (IL-1Ra) molecule in significant concentration by the MSCs and these produced molecules execute the bioactivity of inhibiting IL-1 catabolism (12). This interesting biological approach renders symptomatic relief in pain (13,14). MSCs also support neoangiogenesis through VEGF-A, VEGF-D, HGF, IGF-1, PDGF, PIGF, IL-6, EPO, MCP-1 and cellular proliferation through KGF, FGF-2, VEGF, IGF, PDGF, HGF (11,14).…”
Section: Physiology Of Msc Action In Oa Kneementioning
confidence: 99%
“…This interesting biological approach renders symptomatic relief in pain (13,14). MSCs also support neoangiogenesis through VEGF-A, VEGF-D, HGF, IGF-1, PDGF, PIGF, IL-6, EPO, MCP-1 and cellular proliferation through KGF, FGF-2, VEGF, IGF, PDGF, HGF (11,14). MSCs exerted enhanced chondroprotection through diminished pro-inflammatory mediator production and increased antiinflammatory cytokine production including IDO, PGE2, TGF-β, TSG-6, HGF, NO, HO-1, HLA-G.…”
Section: Physiology Of Msc Action In Oa Kneementioning
confidence: 99%
See 1 more Smart Citation
“…Over past decades, a plurality of studies have found that direct intracerebral (AD) and intraarticular (RA, OP, OA) injection of MSCs confers multiple benefits evidenced by three key features: (1) inflammation remission, (2) stimulation of neotissue formation, and (3) measurable improvements in behavioral outcomes. While these investigations are thoroughly reviewed elsewhere (Duncan and Valenzuela, 2017 ; Kim and Shon, 2020 ), we here discuss current developments toward maximizing the clinical usability and therapeutic potential of MSCs as they apply to AD, inflammatory arthritis, and OP.…”
Section: Mesenchymal Stem Cell (Msc) Therapymentioning
confidence: 99%
“…Moreover, they mediate cartilage repair and scar tissue formation by promoting the secretion of several growth factors, such as epithelial growth factor, insulin-like growth factor-1, fibroblast growth factor, TGF-β, and vascular endothelial growth factor [ 17 ]. These therapeutic functions contribute to the paracrine and immunomodulatory effects of anti-inflammatory and chondroprotective mediators secreted by MSCs [ 19 , 20 ]. Although it has long been known that MSCs produce abundant growth factors and cytokines, some studies have reported that injected MSCs are largely cleared or caught, and hence, only partially act in the target tissue [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%